Financial markets and trading : an introduction to market microstructure and trading strategies - Schmidt, Anatoly B. (Hoboken, N. J. : Wiley, 2011)
'Financial Markets and Trading Strategies covers three main parts: Market organization and microstructure theory, which will contain an overview of modern financial markets for equities, FX, and fixed income. There will be a description on various market types and market price formation with different types of traders and orders. Major theoretical microstructure models will be presented, as also concepts of the agent-based modeling of financial markets and important empirical properties of equity and FX markets. Common trading strategies and back-testing will summarize the concepts used in technical analysis and arbitrage trading (such as pairs trading and mean-reversion strategies). There will be a description of performance criteria and back-testing of trading strategies with re-sampling techniques and an outline of other ideas used in optimal order execution, such as optimal order slicing and maker-versus-taker strategies. The appendix will include Probability distributions and time series analysis. For self-contained presentation, there will be a description of the mathematical methods used in formulating trading strategies and their back-testing. There will be a focus on the linear regression, autoregressive and moving average models, trends, co-integration, and conditional heteroskedasticity. There will also be an introduction to resampling techniques, such as bootstrap and MCMC'--
Includes bibliographical references (p. 180-189) and index.
Keywords: Fixed-income securities; Stock exchanges; Microfinance